Funções inorgânicas e digestão: uma UEPS constituída nas premissas da aprendizagem significativa e da aprendizagem cooperativa - Macuglia, Uliane (2018)
The teaching-learning process of Chemistry in high school has been a challenge for teachers and students. The use of new methodologies, as well as of didactic materials contextualized with the local reality, are an alternative to the traditional model of t he classes, helping to transpose between the chemical concepts and the daily life of the students. The present work constitutes the elaboration, application and analysis of an educational product developed during the professional master's degree program of the Teaching of Sciences and Mathematics of the University of Passo Fundo, linked to the research line Theoretical-Methodological Foundations for the Teaching Science and Mathematics. The objective of the study was to investigate whether the use of a Potentially Significant Teaching Unit, contextualized with the theme related to digestion, was organized in such a way as to meet the premises of meaningful learning conceived by David Ausubel and the cooperative learning developed by the brothers David Johnson and Roger Johnson favors learning the content of inorganic functions in a more meaningful way for students. In order to meet the objective, the study is characterized as qualitative, using three instruments for data collection and analysis: field diary, pre and post intervention questionnaire and poster production by students. For this, the educational product entitled “Inorganic Functions: Let's Digest?” Was developed as a support material for teachers and students, which includes contextualization texts, experimental activities and the conception of inorganic functions acids, bases, salts and oxides. The Potentially Significant Teaching Unit, developed in this dissertation, was applied in a class with 25 first year high school students from a state schoo l in the municipality of Panambi/RS over 10 meetings. The analysis of the collected data allowed to point to the viability of the methodological proposal as evidence of a significant learning, evidenced by the wide participation of the students during the classes, as described in the field diary, in the satisfactory results pointed out in the pre and post intervention questionnaires and in the cooperative work among the students to make the posters, although in the latter, stressed the difficulty in describ ing the chemical reactions involved. The dissertation, accompanied by an educational product intended for high school teachers, was developed from the theoretical discussions that subsidized this dissertation and seeks to be an alternative to the teaching of chemistry by propitiating changes in student and teacher behavior during classes. This product is available at http://educapes.capes.gov.br/handle/capes/206986.